Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1507/endocrj.ej17-0303
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and efficacy of switching from daily dipeptidyl peptidase-4 inhibitors to weekly trelagliptin in patients with type 2 diabetes—Randomized controlled study—

Abstract: Abstract. We compared treatment satisfaction between daily dipeptidyl peptidase-4 (DPP-4) inhibitors and a weekly DPP-4 inhibitor in patients with type 2 diabetes. The study was a 12-week, open-label, randomized, multicenter, controlled trial. Participants were Japanese patients with type 2 diabetes who had received daily DPP-4 inhibitors for more than 3 months. Patients were randomly assigned to a treatment cohort: (1) a group that continued taking daily DPP-4 inhibitors (daily group); or (2) a group that swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…A study of 14 Japanese patients with T2DM who had stable glycemic control on sitagliptin and were switched to trelagliptin showed that blood glucose levels were either maintained or decreased after the switch to trelagliptin [25], suggesting that patients switched to trelagliptin do not experience deterioration in glycemic control. The results of these and other studies [23, 24] support the results of the present study, which showed that trelagliptin was as effective at improving parameters of glycemic control as daily DPP-4 inhibitor treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A study of 14 Japanese patients with T2DM who had stable glycemic control on sitagliptin and were switched to trelagliptin showed that blood glucose levels were either maintained or decreased after the switch to trelagliptin [25], suggesting that patients switched to trelagliptin do not experience deterioration in glycemic control. The results of these and other studies [23, 24] support the results of the present study, which showed that trelagliptin was as effective at improving parameters of glycemic control as daily DPP-4 inhibitor treatment.…”
Section: Discussionsupporting
confidence: 92%
“…A study in 49 Japanese patients with T2DM who had received daily DPP-4 inhibitors for 3 months and were then continued on daily treatment or switched to trelagliptin for 12 weeks found that the change in DTR-QOL total score significantly improved with trelagliptin versus daily DPP-4 inhibitor treatment, and the subscale analysis also showed significantly greater changes with trelagliptin versus daily DPP-4 inhibitor treatment in domain 1 (burden of social activities/personal activities) and domain 2 (anxiety and dissatisfaction with treatment) [23]. Similar to the present study, there was no significant difference in the change in DTSQ total score between groups [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PREFERENCE 4 study documented that treatment-naive Japanese patients preferred (in terms of treatment satisfaction) a DPP-4i to a BG, SU, or α-GI 26. Use of a weekly DPP-4i also improved treatment satisfaction 27 28. However, these are preliminary findings, and additional real-world data from other DPP-4i studies are awaited.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have reported improved treatment satisfaction when patients with T2DM switched from once-daily to once-weekly drugs, based on the Diabetes Treatment Satisfaction Questionnaire [23]. The DTR-QOL instrument that we used is an exact reflection of the patient's satisfaction with treatment, especially in relatively younger patients under the age of 65 years [24], those receiving at most two concomitant drugs for treatment of comorbidities, and those who were treatment naïve before the start of the study [25]. As such, we expected some improvement in patient satisfaction with treatment, but there was no significant improvement in DTR-QOL score in the omarigliptin group.…”
Section: Discussionmentioning
confidence: 99%